Farming With Faith: The Nexus Between Creation/Environment and Religion - Jijimon Alakkalam Joseph (Journal of Dharma, 2025)
Environmental protection is a critical component of the United Nations’ Sustainable Development Goals. Farmers worldwide play a pivotal role in safeguarding the environment, often drawing upon their religious traditions to inform their practices and worldviews. These traditions profoundly influence their relationship with the more-than-human community and their environmental consciousness. Despite this influence, secularization theories have posited that science and rationality would gradually supplant religion in modern societies. Some environmentalists have critiqued anthropocentric religious narratives for exacerbating environmental degradation. Hence, until recently, religious entities have been largely absent from discussions on sustainable development. This paper examines the role of religious communities, spiritual leaders, and sacred texts in shaping the environmental consciousness of Buddhist and Christian farmers in Taiwan. The findings reveal that religious beliefs remain central to shaping individuals’ worldviews and environmental consciousness. Furthermore, the study demonstrates that when religious narratives are interpreted through a lens of reverence for creation, they can foster ecological stewardship